Long-term sequelae secondary to snakebite envenoming: a single centre retrospective study in a Costa Rican paediatric hospital - María Luisa Avila-Aguero; Helena Brenes-Chacon; Jose M Gutierrez; Kattia Camacho-Badilla; Alejandra Soriano-Fallas; Rolando Ulloa-Gutierrez; Kattia Valverde (BMJ Paediatrics Open, 2020)
Objectives Although devastating acute effects associated with snake envenoming are well described, the long-term sequelae resulting from these envenomings have not been adequately addressed, especially in the paediatric population. The aim of our study is to describe the clinical characteristics among paediatric patients in Costa Rica who developed long-term sequelae secondary to snakebite envenoming.Design Retrospective descriptive study of paediatric patients under 13 years who were admitted with a history of a recent snakebite at the National Children’s Hospital in Costa Rica from January 2001 to December 2014.Results We enrolled 74 patients admitted to our centre due to envenoming, and separated those who did not develop sequelae (50 patients) from those who did (24 patients). Of those who presented acute complications during hospitalisation, local wound infection and clinically diagnosed compartmental syndrome were significantly higher in the group that developed sequelae thereafter. Hypertrophic scars (66.7%), functional limitation of affected limb (37.5%) and the need of skin graft (37.5%) were the most common sequelae. The median follow-up of patients with long-term sequelae after discharge was 25.4 months (5.6–59.4). No deaths were reported during this time period.Conclusions Given the high economic, personal and healthcare burden that entails follow-up of these patients, efforts should be carried out to prevent the factors associated with sequelae among the affected population.